Implementation of the constitutional novel on the right of ownership of the people of Kazakhstan to natural resources - Idrysheva, С.К. (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2023)
The article discusses questions about the legal qualification of the people's property rights to natural resources enshrined in the Constitution of the Republic of Kazakhstan and the implementation of this right in practice. For these purposes, a theoretical analysis of issues about subjects and objects of the new category of property rights was carried out, issues of implementing the constitutional innovation in sectoral legislative acts were analyzed, and shortcomings in legislative activity in this area that impeded the implementation of the people's property rights to natural resources were identified. By analyzing the powers of the owner, some essential characteristics and signs of a new category of property rights have been identified, distinguishing this category from other forms of property rights and property rights in general; The people's property right to natural resources is defined as a special property right that has specific characteristics. In this regard, the issues of an indirect method of realizing the people's property rights to natural resources through the use of easement rights of ownership and use of natural resource plots belonging to other persons and receiving a share of the income resulting from their use of natural resources are considered. In the Conclusion, the author made specific conclusions based on the results of the issues considered.